Epstein‐Barr virus prevalence among subtypes of malignant lymphoma in Rwanda, 2012 to 2018. Issue 5 (26th October 2021) - Mpunga, Tharcisse; Clifford, Gary M.; Morgan, Elizabeth A.; Milner, Danny A.; de Martel, Catherine; Munyanshongore, Cyprien; Muvugabigwi, Gaspard; Combes, Jean‐Damien
Abstract: Few data exist on Epstein‐Barr virus (EBV) prevalence across the full spectrum of lymphoma subtypes, particularly in sub‐Saharan Africa. The objective of our study was to test the presence of EBV in a nationally representative sample of malignant lymphomas diagnosed in the Butaro Cancer Center of Excellence (BCCOE) in Rwanda. Of 102 Hodgkin (HL) and 378 non‐Hodgkin lymphomas (NHL) diagnosed in BCCOE between 2012 and 2018, 52 HL and 207 NHL were successfully tested by EBV‐encoding RNA in situ hybridization. EBV prevalence was 54% in HL, being detected in all classical HL subtypes: mixed‐cellularity (n = 3/8), nodular‐sclerosis (n = 7/17) and lymphocyte‐rich (n = 2/3). EBV prevalence was 9% in NHL, being 10% among 158 B‐cell NHL, 3% among 35 T‐cell NHL and the single NK‐cell NHL was EBV‐positive. Among B‐cell NHL, EBV was present in the majority of Burkitt (n = 8/13), and was also rarely detected in follicular (n = 1/4) and acute B‐cell lymphoblastic (n = 1/45) lymphomas. Five of the 45 (11%) diffuse large B‐cell lymphomas (DLBCLs) were EBV‐positive, including three out of five plasmablastic lymphoma (PBL). Of 39 HL and 163 NHL of known human immunodeficiency virus (HIV) status, 2 (5%) and 14 (9%) were HIV‐positive, respectively, of which only four were also EBV‐positive (2 PBL, 2 HL). In summary, we report rare regional‐level data on the association of EBV with classical HL, Burkitt and DLBCLs, and report sporadic detection in other subtypes possibly related to EBV. Such data inform the burden of disease caused by EBV and can help guide application of future advances in EBV‐specific prevention and therapeutics. Abstract : What's new? Estimates of Epstein‐Barr virus (EBV) prevalence across the full spectrum of malignant lymphoma subtypes are rare, particularly in sub‐Saharan Africa. Here, EBV prevalence was investigated across all lymphoma subtypes in a nationally representative sample of lymphomas from Rwanda. Analyses confirm estimates of EBV‐attributable fractions for Hodgkin's lymphoma and Burkitt's lymphoma, and support a causal role for EBV in a fraction of diffuse large B‐cell lymphomas and other rare subtypes. Insight into EBV‐associated lymphoma burden in sub‐Saharan Africa could open the way to improved prevention and treatment.